Assessing the community-based tourism potentials of Romblon, Philippines: A structural equation model - Avi Ben Pestañas Andalecio; Ginelle Aira T. Rose; Mark Ryan J. Isidro; Ana Therese Jin-ju A. Lee; Katrina Luz P. Martinez; Rafael Anton Manuel M. Dionisio; Raphael Frederick M. Tamayo; Justin Miccaela T. Tampolino; Audrey Veronica Wednesday T. Valentin (School of Tourism, Universitas Ciputra Surabaya, 2022)
Community-Based Tourism is seen for having a huge impact on rural communities in the Philippines and many countries. It is generally known for its pro-poor implications that deliver socio-cultural, ecological, and economic benefits to steer a community if directed with strong policies. CBT has a great potential on elevating the said aspects of a locality for community development. Hence, the researchers attempted to comprehensively determine the perceptions of key actors in CBT with quantitative approaches to shed light on its costs and benefits in the communities of Romblon province in the Philippines. Through quota sampling, a total of 400 residents were surveyed to determine their positive and negative perceptions towards CBT. Structural Equation Modeling was utilized as the statistical analysis tool to impute relationships on the latent variables; sustainable tourism development, politico-administrative affairs and climate, and citizen participation. The model provided empirical evidence that CBT activities positively affect the latent variables in Romblon province. The findings contributed to the great importance of politico-administrative affairs and climate as a support system to enhance tourism laws and programs. The authors, moreover, advocated for further improvements on sustainable tourism development and citizen participation. Among recommendations, in order to assist the tourism stakeholders in the development of CBT, this study proposed sustainable tourism programs focused on enhancement of the quality of life of the locals, fostering collaborations among institutions and the people, and for a sustainable growth of Romblon province